(untitled) (Journal of Nepalese Business Studies, 2016)
Entrepreneurship is the engine for social and economic growth of any society. It drives people toward wealth and job creation, which leads to better lives for people in the society. There has been growing interest in entrepreneurship research recently. This paper attempted to assess the impact of family in Nepalese society. This was viewed as essential in a country in which more than 125 ethnic communities are found. The findings show that family has some impact in people to become entrepreneurship but it was not strongly substantiated by statistical tests. It was found that entrepreneur’s parental profession plays some role in entrepreneurship development in Nepal which was similar to some findings that parental profession plays vital role in the choice of profession in children. Journal of Nepalese Bussiness Studies Vol. 9, No. 1, 2015 pp. 37-47